Europeanization in Turkey: stretching a concept to its limits? - Börzel, Tanja; Soyaltin-Colella, Digdem (2012)
Abstract: Research on Europeanization and domestic change has moved south-eastwards and was provided with another real-world experiment when it has meet with Turkey. This paper explores to what extent Europeanization approaches travel to Turkey, which does have a membership perspective that looks, however, ever less credible. The first part outlines the main findings of research on ‘External Europeanization’ focusing on factors that have limited or at least qualified the domestic impact of the EU in the Central and Eastern European (CEE) and Western Balkan (WB) accession countries. The paper, then, discusses to what extent Europeanization approaches need further qualification when applied to Turkey, which squares on democracy with the Western Balkans (with the exception of Croatia), but whose statehood is less limited. We argue that existing Europeanization approaches, largely, account for the overall moderate degree of Europeanization in Turkey. Yet, selective and differential domestic chan